Electronic records management (ERM) practices at The Malaysian Federal Ministries: exploring the fundamental organizational and professional issues / Irwan Kamaruddin Abd Kadir - Abd Kadir, Irwan Kamaruddin (Institute of Graduate Studies, UiTM, 2014)
This study is an attempt to gain greater understanding of the importance of departmental records officers’ (in Malaysian Government they are called ‘Pegawai Rekod Jabatan’ (PRJ)) roles and responsibilities on electronic records (e-records). The study adopted a case study approach that combined both quantitative and qualitative data. Quantitative data were gathered in the first phase of the study from 45 agencies under the Prime Minister’s Department. In the second phase of the study, qualitative data were gathered from faceto- face interviews with three PRJs from three agencies under the Prime Minister’s Department. To verify data gathered in the second phase of the study, four focus group (FG) discussions with 120 PRJs from 24 ministries and related agencies were conducted in the third phase of the study.